PEMANFAATAN APLIKASI PREZI DI LEMBAGA BIMBINGAN BELAJAR GAMA UI CABANG DUREN TIGA JAKARTA SELATAN - Nur Arifiya; Sri Hartini; Syafa’atun Syafa’atun (Abdimas Siliwangi, 2020)
GAMA UI tutoring is one of the educational institutions that provide additional tutoring outside school hours. The condition of students who take tutoring are students who have limitations in understanding learning material in school. So it needs to be given extra hours of study outside school hours. The existence of technology is able to make the teaching and learning process more interesting and by utilizing learning applications can facilitate teachers in managing and delivering messages to students. So that a positive impact on learning, because with a more attractive appearance children tend to be more understanding. One of the learning media that can be used is the Prezi application, the Prezi application can be used online and offline. Thus the purpose of community service activities aims to provide information related to the application of Prezi to GAMA UI tutors and provide short training utilizing the Prezi application both online and offline. So as to increase understanding and motivation to learn children tutoring participants in GAMA UI. The implementation of community service activities is carried out in three stages, the first is preparation by direct observation, the second is the delivery of material, and the last is evaluation. After this activity, it was seen that the teaching staff were very enthusiastic to use the Prezi application in the learning process in the future